2013
DOI: 10.1016/j.applthermaleng.2012.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of pumped thermal electricity storage

Abstract: The increasing use of renewable energy technologies for electricity generation, many of which have an unpredictably intermittent nature, will inevitably lead to a greater need for electricity storage. Although there are many existing and emerging storage technologies, most have limitations in terms of geographical constraints, high capital cost or low cycle life, and few are of sufficient scale (in terms of both power and storage capacity) for integration at the transmission and distribution levels. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(98 citation statements)
references
References 6 publications
0
98
0
Order By: Relevance
“…However, this would require very short time steps and is in any case unnecessary since the unsteady gas terms in Eqs. (3)(4)(5) are generally very small. For example, in Eq.…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this would require very short time steps and is in any case unnecessary since the unsteady gas terms in Eqs. (3)(4)(5) are generally very small. For example, in Eq.…”
Section: Governing Equationsmentioning
confidence: 99%
“…For accurate calculations Eqs. (3)(4)(5)(6) should be solved in a coupled fashion using, for example, a finite--volume time--marching approach. However, this would require very short time steps and is in any case unnecessary since the unsteady gas terms in Eqs.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thess [32] performed a theoretical work that includes "endoreversible" analysis of a generic system while White et al [33] and McTigue et al [34] studied thermodynamic aspects of Pumped Thermal Electricity Storage.…”
Section: Figure 2 Ptes Unit Proposed In [33]mentioning
confidence: 99%
“…Peterson [12] and Henchoz et al [13] noted the effectiveness of sub-ambient temperature ETES. White et al [14] investigated the thermodynamic aspects of a pumped thermal electricity storage system, and showed that highly efficient compression and expansion processes are clearly required to obtain a satisfactory cycle efficiency. Meanwhile, the transcritical CO 2 Rankine cycle has been proposed to replace the Rankine cycle as the thermodynamic cycle, which is allowing for higher roundtrip efficiency in heat exchange process [15].…”
Section: Introductionmentioning
confidence: 99%